PENGEMBANGAN MATERI RESILIENSI - Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This study aims at drafting material about resilience needed for highschool students in terms of the clarity of the material , the material systematics , imagesupport , renewal of the material , and completeness of the materials and support vidio /game . Before the researchers gave the material to the students , the researchers firstdemonstrated the results of his material to the supervisor I and II lecturers , teachers oncounseling where researchers do research as much as 5 people . After much pass arevision with the suggestions by experts subsequent researchers provide resiliencematerial is 3x meeting . Then, after the researchers gave the students teaching materialssuch materials provide an assessment of the resilience of a given material. Of the valuegiven by experts and students of the obtained results of calculations for clarity aspectsof material gain values including very clear category with a score of 4.45 , for thesystematic aspects of material gain values including very systematic category with ascore of 4.50 , to aspects of image support received grades 4.67 which included a verygood category , for the aspects of renewal of the material received grades 4.54 whichincluded a very new category , and for aspects of the completeness of the materialsobtained a value of 3.94 which included a complete category , and to support the games/ vidio scored 3.92 which includes support category , whereas for all aspects of thematerial assessment showed that the materials developed already meet the criteria areexpected to obtain a value of 4.38 which included a very good category.Keywords:Material development , resilience